2015
DOI: 10.1021/acs.jpca.5b07244
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonded Networks in Hydride Water Clusters, F(H2O)n and Cl(H2O)n: Cubic Form of F(H2O)7 and Cl(H2O)7

Abstract: The anion-water bonds and hydrogen bonds between water molecules in X(-)(H(2)O)(n) (X = F and Cl, n = 3-7) clusters are analyzed by evaluating the charge-transfer (CT) and dispersion terms for every pair of ions and molecules with the perturbation theory based on the locally projected molecular orbitals. In particular, the relative stabilities and the bond strengths in all 11 distinct cubic X(-)(H(2)O)(7) isomers are analyzed by classifying the ligand water (L) with the numbers of the donating (n) and acceptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In previous studies 23,34,41 , the evaluated energy is shown to be close to the counterpoise (CP) corrected HF binding energy if the augmented basis functions are used. In previous studies 23,34,41 , the evaluated energy is shown to be close to the counterpoise (CP) corrected HF binding energy if the augmented basis functions are used.…”
Section: Relative Energiesmentioning
confidence: 79%
See 1 more Smart Citation
“…In previous studies 23,34,41 , the evaluated energy is shown to be close to the counterpoise (CP) corrected HF binding energy if the augmented basis functions are used. In previous studies 23,34,41 , the evaluated energy is shown to be close to the counterpoise (CP) corrected HF binding energy if the augmented basis functions are used.…”
Section: Relative Energiesmentioning
confidence: 79%
“…In previous studies 23,34,41 , the evaluated energy is shown to be close to the counterpoise (CP) corrected HF binding energy if the augmented basis functions are used. 41 The corresponding E apprCP_HF+MP2 /aug-cc-pVxZ binding energies are -57.6 (x=D), -61.2 (x=T), -62.1 (x=Q) and -62.5 (x=5) kJ mol −1 for Cl − (H 2 O) , 42 and -112. 41 The corresponding E apprCP_HF+MP2 /aug-cc-pVxZ binding energies are -57.6 (x=D), -61.2 (x=T), -62.1 (x=Q) and -62.5 (x=5) kJ mol −1 for Cl − (H 2 O) , 42 and -112.…”
Section: Relative Energiesmentioning
confidence: 79%
“…72 The electronic structure model places bromide at the periphery of a octahydrate cluster 3a8, similar to minimum structures calculated for hepta-and octahydrated chloride. 73,74 The mean oxygenbromine distance in the static model of octahydrate 3a8 according to theory is 3.32 Å ( Figure 10).…”
Section: Hydrogen Bonding To Bromidementioning
confidence: 93%
“…1,4,12,13,22,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Generally, the hydration of anions is less of a focus than the situation of cations, although the dynamics of water molecules in the first hydration shell of anions is important in aqueous phase chemical reactions in which anions are involved 27,28,[35][36][37][38][39][40] . There are several examples of Cl − involved in simple contact ion pair/solvent-separated ion pair dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…There are several examples of Cl − involved in simple contact ion pair/solvent-separated ion pair dynamics. 1,4, [11][12][13][14][15][16][17][18][19][20][21][22][23][27][28][29][30]34 In contrast to the hydration of cations, the work of Kim et al 35 and Matsuzawa et al 36 showed that the hydration of Cl − prefers surface structures. Laage and Hynes et al found the mean residence time (MRT) of water molecules around the shell of Cl − is approximately 7−11 ps, supporting a labile, nonrigid Cl − hydration shell.…”
Section: Introductionmentioning
confidence: 99%